Effects of milk feeding levels and starter feed crude protein and fat contents on growth performance, rumen fermentation, and purine derivative excretion in urine of dairy calves - M. Yazdanyar; M. Kazemi-Bonchenari; M. Eghbali; A. Sadeghisharif; A. Jafari; M. Molaei; M. Kornasi; H. Khalilvandi-Behroozyar; M.H. Ghaffari (Journal of Dairy Science)
ABSTRACT: The study investigated how different milk feeding levels and the composition of the starter feed interact to influence growth performance, rumen fermentation, certain blood parameters, and the excretion of purine derivatives in the urine of dairy calves. A total of 72 female Holstein dairy calves (mean BW = 40.6 ± 1.9 kg) were assigned to a completely randomized design with a 2 × 3 factorial arrangement. The starter diets differed in CP (20% vs. 24%, DM basis) and total crude fat (CF, ether extract; 3.0% vs. 5.5%, DM basis). The 6 treatment groups were as follows: moderate milk with 20% CP and 3% CF (MM-CON), moderate milk with 24% CP and 3% CF (MM-HCP), moderate milk with 20% CP and 5.5% CF (MM-HCF), high milk with 20% CP and 3% CF (HM-CON), high milk with 24% CP and 3% CF (HM-HCP), and high milk with 20% CP and 5.5% CF (HM-HCF). Calves had free access to a starter feed and water and were weaned on d 53 but remained in the study until d 73. Calves fed the HM-HCF diet had the lowest starter feed intake both pre- and postweaning, and calves fed the HM-HCP and HM-CON diets had the greatest preweaning ADG. Feed efficiency and protein intake were also lowest in HM-HCF calves before weaning, whereas fat intake was consistently greater in calves fed HCF diets. Calves fed the HM-HCP diet had the largest body size, heart girth, and withers height at weaning and at the end of the study, whereas the HM-HCF calves had the smallest. Rumen fermentation profiles showed that total VFA concentrations were lowest in HM-HCF calves, along with an increased acetate-to-propionate ratio. In contrast, HM-HCP calves had a greater molar proportion of propionate preweaning and butyrate postweaning, along with a greater proportion of branched-chain VFA in high-CP diets, indicating more efficient microbial activity in the rumen. Urinary analyses were consistent with these results, as HM-HCF calves had the greatest creatinine levels and lowest urine volumes, whereas HM-HCP calves showed the greatest excretion of the microbial protein synthesis markers allantoin and uric acid. Blood metabolite analysis showed that glucose levels were greater in HM-fed calves preweaning, whereas BHB levels were lowest in HM-HCF calves. Overall, diets with high milk allowance, high CP (24% of DM), and moderate fat (3% of DM) may promote growth, rumen function, and metabolic efficiency, whereas high-fat starter diets (5.5% of DM) may limit feed intake and growth of dairy calves.